2017
DOI: 10.1093/cercor/bhx030
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Relationship Between Functional Connectivity and Intracortical Myelin in the Human Cerebral Cortex

Abstract: Research in the macaque monkey suggests that cortical areas with similar microstructure are more likely to be connected. Here, we examine this link in the human cerebral cortex using 2 magnetic resonance imaging (MRI) measures: quantitative  T1 maps, which are sensitive to intracortical myelin content and provide an in vivo proxy for cortical microstructure, and resting-state functional connectivity. Using ultrahigh-resolution MRI at 7 T and dedicated image processing tools, we demonstrate a systematic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
254
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(318 citation statements)
references
References 112 publications
37
254
2
Order By: Relevance
“…The authors found that the T1w/T2w–derived map indeed yielded substantially improved fits compared with randomized surrogate heterogeneity maps. These findings identify the T1w/T2w map as a preferential axis for heterogeneity shaping FC (102,103). More broadly, this study provides a useful path forward in hypothesis-driven whole-brain modeling by using the topography of a heterogeneity map to parametrize local circuit properties across brain areas.…”
Section: Importance Of Cortical Heterogeneitymentioning
confidence: 66%
“…The authors found that the T1w/T2w–derived map indeed yielded substantially improved fits compared with randomized surrogate heterogeneity maps. These findings identify the T1w/T2w map as a preferential axis for heterogeneity shaping FC (102,103). More broadly, this study provides a useful path forward in hypothesis-driven whole-brain modeling by using the topography of a heterogeneity map to parametrize local circuit properties across brain areas.…”
Section: Importance Of Cortical Heterogeneitymentioning
confidence: 66%
“…A similar spatial distribution has been described for MRI-based measures of cortical thickness [12] and myelinated thickness [29]. Cortical thickness coarsely tracks changes in cytoarchitecture [30] and myelin content [25], and can be viewed as a pragmatic surrogate for cortical microstructure [12].…”
Section: Glossarymentioning
confidence: 78%
“…In addition, the spatial layout of the principal gradient aligns with the human microstructural gradient described in the previous section. A direct comparison of the principal gradient of functional connectivity and intracortical myelin content revealed a systematic spatial relationship [25]. Global connectivity patterns thus reveal a sensorimotor-to-transmodal gradient that is strongly related to a gradient in local microstructural features and the intrinsic geometry of the cortex.…”
Section: Glossarymentioning
confidence: 84%
See 2 more Smart Citations